1999
DOI: 10.1063/1.124914
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulation of thermal conductivity of silicon nanowires

Abstract: We investigate the thermal conductivity of silicon nanowires based on molecular dynamics (MD) simulations. The simulated thermal conductivities of nanowires with square cross sections are found to be about two orders of magnitude smaller than those of bulk Si crystals in a wide range of temperatures (200–500 K) for both rigid and free boundary conditions. A solution of the Boltzmann transport equation is used to explore the possibility of explaining the MD results based on boundary scattering.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
316
3

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 419 publications
(329 citation statements)
references
References 19 publications
10
316
3
Order By: Relevance
“…1 κ is the thermal conductivity along the chain length, V is the system volume, Q z is the volume averaged heat flux along the chain axis direction (z-direction), and t is time. This approach has been used extensively to study the thermal conductivity of many different classes of materials and has shown good agreement with experiments and first principles based approaches 23,[40][41][42][43] . The quantity Q z (t)Q z (t + ′ t ) in Eq.…”
Section: Divergent Thermal Conductivity In Polymer Chainsmentioning
confidence: 90%
See 1 more Smart Citation
“…1 κ is the thermal conductivity along the chain length, V is the system volume, Q z is the volume averaged heat flux along the chain axis direction (z-direction), and t is time. This approach has been used extensively to study the thermal conductivity of many different classes of materials and has shown good agreement with experiments and first principles based approaches 23,[40][41][42][43] . The quantity Q z (t)Q z (t + ′ t ) in Eq.…”
Section: Divergent Thermal Conductivity In Polymer Chainsmentioning
confidence: 90%
“…Although only 20% of the cases diverged, if one considers calculation of the ensemble average, the averaged thermal conductivity will diverge as a result. We calculated the thermal conductivity for 10,20,30,40, 80, 90, 120, and 150 unit cell chains, and the 30, 90 and 150 unit cell length chains exhibited divergent thermal conductivity. Similar to Henry and Chen's 23 results for PE, there were some simulations that exhibited clear convergence and others that exhibit clear divergence, with many cases falling in between these extremes.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the thermal conductivity of SWSNTs shown in Fig. 6 is much larger than that of Si nanowires (from 1 to 4 W/m·K) as reported in work by Chen and Volz [9]. This is attributed to the entirely different atomic structure of SWSNTs from Si nanowires.…”
Section: Thermal Conductivity and Specific Heat Of Swsntsmentioning
confidence: 50%
“…For numerical studies, molecular dynamics (MD) simulation has been widely employed to study the thermal transport in CNTs [2,8]. Previous study by Chen and Volz [9] explored the thermal conductivity of another 1D structure allotrope of Si nanowires using equilibrium MD (EMD) simulation. The result showed the thermal conductivity was about two orders of magnitude smaller than that of bulk Si.…”
Section: Introductionmentioning
confidence: 99%
“…Studies on silicon nanowires [7][8][9][10][11] have shown that diameter lowering induces thermal conductivity decrease. Theoretically, this observation is well described by an important number of phonon interactions with the medium boundaries.…”
Section: Nanowires Modelingmentioning
confidence: 99%